Βιβλιοκρισία: JOSEPH SHATZMILLER, Cultural Exchange: Jews, Christians, and Art in the Medieval Marketplace, Princeton University Press, Princeton and Oxford, 2017, 185 σελ., 30 εικ., ISBN 978-0-691-17618-5 - ΔΡΑΚΟΠΟΥΛΟΥ, Eυγενία (Byzantina Symmeikta, 2017)
JOSEPH SHATZMILLER, Cultural Exchange: Jews, Christians, and Art in the Medieval Marketplace, Princeton University Press, Princeton and Oxford, 20172, 185 σελ., 30 εικ., ISBN 978-0-691-17618-5